Registration Of The Buying And Sale Of Land Rights Post Implementation Of The Presidential Instruction Number 1 Of 2022 Concerning Optimization Of The Implementation Of The National Health Security Program - WESNA, Putu Ayu Sriasih; WIJAYA, Edward (Indonesia Strategic Sustainability, 2022)
Land sales and purchases must be completed prior to the PPAT that intended to give legal clarity and protection to the owner of a land parcel or other registered right so that he may readily establish his ownership of the relevant right and for the efficient administration of property. Fundamental guidelines that must be followed when purchasing and selling land are the transaction procedure and the certificate document's validity. The government released Presidential Instruction of the Republic of Indonesia (Inpres) Number 1 of 2022 on Optimum Implementation of the National Health Insurance Program (JKN). The Presidential Instruction regulates the requirements for managing a number of public services such as buying and selling land, making SIM, STNK, SKCK, Haji and Umrah which must be registered as BPJS Health participants. In the Inpres Number 1 of 2022, the government instructed 30 ministries/agencies to require JKN-KIS for various purposes to ensure that all people are protected by health insurance. Some of these policies seem to have no relationship or connection, but they are actually very closely correlated. The government wants to ensure that all levels of society have health insurance, especially the upper middle class who have not been registered with the JKN-KIS program. BPJS Health participant cards is one of the requirements for buying and selling land. The BPJS Health participant card is a requirement in the application for registration services for the transfer of land rights or ownership rights to flat units due to buying and selling.